A Flexible Quasi‐Solid‐State Asymmetric Electrochemical Capacitor Based on Hierarchical Porous V2O5 Nanosheets on Carbon Nanofibers. Issue 17 (1st July 2015) - Li, Linlin; Peng, Shengjie; Wu, Hao Bin; Yu, Le; Madhavi, Srinivasan; Lou, Xiong Wen (David)
<x xml:space="preserve">Abstract</x> The development of 3D nanoarchitectures on flexible current collectors has emerged as an effective strategy for preparing advanced portable and wearable power sources. Herein, a flexible and efficient electrode is demonstrated based on electrospun carbon fibers (ECF) substrate with elaborately designed hierarchical porous V2O5 nanosheets (V2O5–ECF). The unique configuration of V2O5–ECF composite film fully enables utilization of the synergistic effects from both high electrochemical performance of V2O5 and excellent conductivity of ECF, endowing the films to be an excellent electrode for flexible and lightweight electrochemical capacitors (ECs). Benefiting from their intriguing structural features, V2O5–ECF and ECF films, directly used as electrodes for flexible asymmetric quasi‐solid‐state electrochemical capacitors, achieve superior flexibility and reliability, enhanced energy/power density, and outstanding cycling stability. Moreover, the ability to power light‐emitting diodes (LED) also indicates the feasibility for practical use. Therefore, it is believed that this novel design may find promising application in flexible devices in future.